Developing a Seasonal Cash Demand Simulation for Agricultural Cooperatives (Village Unit Cooperative) in Indonesia - Santoso, Budi (Gadjah Mada International Journal of Business, 2012)
Irrespective of the success of the Indonesian Government to achieve self-sufficiency of rice in 1985, and the rice price stabilization, paddy growers still suffer from a very low price for their produce. Koperasi Unit Desa (KUDs) âin Indonesian, or Village Unit Cooperative (VUC) have been entrusted with the marketing of rice paddies although their performance has always been less than satisfactory. One problem experienced by the KUDs is not having sufficient cash to purchase and process paddies into rice. The purpose of this study is to develop and validate a simulation model to represent cash flows during one paddy plantation season for a KUD (VUC). The simulation model is a decision support tool that enables a KUDâs (VUC) management to determine the maximum quantity of paddies to be purchased; the minimum borrowing and additional borrowing; and the earnings before taxes. An investigator- administrated questionnaire was used to collect historical data of the twenty randomly selected KUDs (VUC) on Lombok Island to validate the sub-models of the simulation model. The Kolmogorov- Smirnov Goodness of Fit (two-sample), linear regression, correlation and t- tests were used to validate the simulation model. The validation results have shown that the sub-models of the simulation model are valid, and these may contribute to the valid results of the simulation model. This study has found that the limitations of the paddy storage building, drying floor, and milling machine owned by the KUDs (VUC) may restrict the KUDs (VUC) from buying the entire paddies harvested. Therefore, further research is needed to find out the minimum capacities of those facilities enabling the KUDs (VUC) to work efficiently.Keywords: agricultural cooperatives (Village Unit Cooperative); seasonal demands; cash flows; simulation; validation